What Makes a Good Tenant?: Squatters and migrants resisting housing discrimination in Warsaw - Kamil Kuhr (Radical Housing Journal, 2019)
In this paper, I pose a question of whether it would be possible to build an alliance of the migrant tenants and squatters in Warsaw to resist housing discrimination. The socio-political framework for my answer includes housing, financial, and asylum crises. By referring to the ideas of “political hegemony” (Mouffe) and “the distribution of the sensible” (Rancière), I show that housing discrimination is the result of the neoliberal narrative that puts the owner of a flat in a position of power. An intersectional perspective allows me to examine how different identities (gender, ethnicity, nationality, etc.) are embodied by tenants searching for flats. Finally, I interpret the relations between squatting and migrant communities as “a critical alliance” (Butler) based on the idea of “nonheroic disobedience and weak resistance” (Majewska).